Factors Affecting the Preference of Millenial Muslim Generation Toward Halal Cosmetics in East Kalimantan - Fitria Rahmah (Al-Tijary, 2021)
The halal industry has experienced significant development in recent years, including cosmetic industry and halal pharmaceutical which has increased quite drastically nowadays. This study aims to determine the factors that influence the preference of millennial generation for halal cosmetics in East Kalimantan, including religiosity variable, halal awareness and halal certification. This research can be categorized as field research with quantitative method. The data used were from primary data collected directly from respondents using google form, while the secondary data were obtained from articles, books, internet. The data which collected was then processed in several stages of testing, namely validity and reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that the religiosity variable had a positive but not significant effect on the preference of millennial generation for cosmetics, while the halal awareness and halal certification variable had a positive and significant effect on the millennial generation's preference for halal cosmetics in East Kalimantan.